Turismo cultural en Colombia - Luisa Fernanda Meneses Gelves; Julián Stevan Mariño Bohórquez; Blanca Mery Rolon Rodríguez (Mundo Fesc)
The following article presents the exhaustive research conducted in the city of Cúcuta to gather information on cultural tourism, its implications, its contributions, and the sustainable development it generates. This research was conducted by reviewing various bibliographic sources, such as articles and newspapers, using Google Scholar to gather up-to-date, reliable, and accurate information on cultural tourism. The results revealed the importance of the tourism sector in Colombia, as it is an industry in constant movement, growth, and evolution, bringing with it economic, social, cultural, and sustainable development contributions. Tourism today is more than just a trip; it is based on a life experience, which has led to the care and preservation of the country's cultural heritage, as it is what captures the attention of tourists and compels them to visit a certain place. "Tourists choose cities that present greater movement and a typical resemblance to the destinations, which is reflected in their music, food, trends, and even idioms." This sector achieves what others cannot: the blending of cultures. It allows us to learn about history, customs, and more. It strengthens ties between peoples focused on their progress and development.